2005
DOI: 10.1051/0004-6361:20042019
|View full text |Cite
|
Sign up to set email alerts
|

A survey for Fe 6.4 keV emission in young stellar objects in $\mathsf{\rho}$ Oph: The strong fluorescence from Elias 29

Abstract: Abstract.We report the results of a search for 6.4 keV Fe fluorescent emission in Young Stellar Objects (YSOs) with measured accretion luminosities in the ρ Oph cloud, using the existing Chandra and XMM-Newton observations of the region. A total of nine such YSOs have X-ray data with sufficiently high S /N for the 6.4 keV line to be potentially detected if present. A positive detection of the Fe 6.4 keV line is reported for one object, Elias 29, in both the XMM-Newton and the Chandra data. The 6.4 keV line is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 17 publications
4
30
1
Order By: Relevance
“…In this case, for favourable disk inclination angles (near face-on, i = 0 • -30 • ), W 6.4 keV varies approximately between 120 and 200 eV for an incident spectrum spectral index Γ = 2.3 to 1.3. This interpretation of the origin of the fluorescent Fe K emission was also proposed by Favata et al (2005b) for Elias 29, whose accretion disk was shown to be in a relatively face-on orientation (i < 60 • ) by Boogert et al (2002). This interpretation cannot, however, easily explain the current set of data.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…In this case, for favourable disk inclination angles (near face-on, i = 0 • -30 • ), W 6.4 keV varies approximately between 120 and 200 eV for an incident spectrum spectral index Γ = 2.3 to 1.3. This interpretation of the origin of the fluorescent Fe K emission was also proposed by Favata et al (2005b) for Elias 29, whose accretion disk was shown to be in a relatively face-on orientation (i < 60 • ) by Boogert et al (2002). This interpretation cannot, however, easily explain the current set of data.…”
Section: Discussionsupporting
confidence: 64%
“…Given that the thermal spectrum of stellar sources is generally steeper than a power-law spectrum with Γ ∼ 2.0 (e.g. Favata et al 2005b;Giardino et al 2007), photospheric emission can hardly explain the observed equivalent widths. George & Fabian (1991) show that higher equivalent widths for the fluorescent Fe K line can be obtained if the cold material is distributed in a centrally illuminated disk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A meaningful sample of CTTS fluorescent signatures is available , with several unexpected features deserving further study. Specifically, strong fluorescence in the Class I protostar Elias 29 (in the ρ Oph region) appears to be quasi-steady rather than related to strong X-ray flares (Favata et al 2005); even more perplexing, the 6.4 keV line is modulated on time scales of days regardless of the nearly constant stellar X-ray emission; it also does not react to the occurrence of appreciable X-ray flares in the light curve (Giardino et al 2007). The latter authors suggested that here we see 6.4 keV emission due to non-thermal electron impact in relatively dense, accreting magnetic loops.…”
Section: X-ray Fluorescencementioning
confidence: 98%